Muslim Consumer Protection Against The Inclusion Of Halal Labels Not Registered With BPJPH - Kusuma, Dewi Puja; Khoiruddin, Khoiruddin; Nurkholidah, Susi (Universitas Islam Negeri Raden Intan Lampung, 2024)
The current progress of the economic sector has resulted in a high level of community needs, thus encouraging business actors to be more creative in creating businesses. One of them can be seen by the number of processed food traders in Bandar Lampung City, especially in Kota Baru Village. However, in running their business, the majority of food traders have not realized the importance of fulfilling halal standards for the products sold and also implementing protection for consumers. So to provide legal certainty, Law number 33 of 2014 concerning Halal Product Assurance was promulgated. The guarantee of the implementation of halal products aims to provide comfort, security, safety, and certainty of the availability of halal products for the public in consuming and using products, as well as increasing added value for business actors to produce and sell halal products. The study is focused on the discussion of how the form of protection of Muslim consumers against the inclusion of halal labels that are not registered with BPJPH for MSMEs in the culinary sector in Kota Baru Village, Bandar Lampung City.with a comparative analysis research method with Sampling Techniques In this study with the sampling technique used, namely, Non-probability sampling with purposive sampling techniques. The results of the study show that there are still many MSME actors who have included their halal labels and have been running their business activities but have not been registered with BPJPH because the cost aspect that must be incurred by MSME actors in the process of applying for halal certification is also an obstacle for them. As well as the lack of knowledge from business actors about the importance of registering halal certification on their processed products.Keywords: Muslim Consumer Protection; Halal Products; MSMEs